Perceived Usefulness, Perceived Risk, Customer Experience, and E-Satisfaction in E-Commerce Repurchase Intention - Susi Evanita; Nadhila Sari; Zul Fahmi (Business and Applied Management Journal, 2026)
The rapid growth of e-commerce in Indonesia has increased competition among digital platforms, making customer retention and repurchase intention increasingly important. This study examines the influence of perceived usefulness, perceived risk, and customer experience on repurchase intention, with digital satisfaction as a mediating variable. A quantitative causal approach was used by collecting data from 240 e-commerce users. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that customer experience has a positive effect on digital satisfaction (β = 0.596; p < 0.001) but a negative effect on repurchase intention (β = -0.297; p = 0.001), indicating a possible tendency to switch in a competitive digital market. Electronic satisfaction has the strongest positive effect on repurchase intention (β = 0.784; p < 0.001). Perceived risk negatively affects e-satisfaction (β = -0.370; p < 0.001) and repurchase intention (β = -0.424; p < 0.001), while perceived usefulness positively affects e-satisfaction (β = 0.096; p = 0.017) and repurchase intention (β = 0.059; p = 0.023). E-satisfaction also significantly mediates the influence of customer experience, perceived risk, and perceived usefulness on repurchase intention. This study extends research based on the Technology Acceptance Model by integrating the mechanisms of risk, experience, and satisfaction.